2016
DOI: 10.3844/ajabssp.2016.2.12
|View full text |Cite
|
Sign up to set email alerts
|

GIS Mapping of Basal Stem Rot Disease in Relation to Soil Series Among Oil Palm Smallholders

Abstract: Basal Stem Rot (BSR) is a disease caused by fungus which affect oil palm tree. This study aims to visualize the geographical distribution of BSR incidence among oil palm smallholders in Selangor using Geographical Information System (GIS) and its relationship to the type of soil series. The geographical distribution of BSR incidence of smallholders in Selangor were mapped using 168 Global Positioning System (GPS) coordinate of possible infected area. The methodology followed in finding the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…; Parthiban et al. ). On the other hand, levels of nutrient elements in plants have been related to either susceptibility or resistance of plants against diseases (Marschner ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Parthiban et al. ). On the other hand, levels of nutrient elements in plants have been related to either susceptibility or resistance of plants against diseases (Marschner ).…”
Section: Introductionmentioning
confidence: 98%
“…Implementation of effective control strategies on stem rot diseases requires better understanding of its epidemiological aspects, such as distribution of the pathogens and plant's nutrients levels. Spatial distribution patterns of the Ganoderma species may provide useful information that would aid in the design of epidemiological studies and development of more accurate site-specific sampling programmes (Van de Lande and Zadoks 1999;Azahar et al 2011;Parthiban et al 2016). On the other hand, levels of nutrient elements in plants have been related to either susceptibility or resistance of plants against diseases (Marschner 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Reports on BSR disease in various soil types are alarming and geographical distribution mapping of disease incidence such as in Selangor, Malaysia did not show any relationship to different types of soil series [14]. Although peat soil was once assumed to be non-conducive for BSR disease development [15], various studies regarding BSR and USR incidence in oil palm planted on peat have been reported [8,9,14,16]. Out of the total 5.85 million hectares of oil palm planted area in Malaysia, only 13% are planted on peat where most can be found in Sarawak [17].…”
Section: Introductionmentioning
confidence: 99%
“…Selangor state is one of the thirteen states of Malaysia and is located in West Malaysia at the estimated coordinate 3.0738° N, 101.5183° E. The total area is about 8000 square kilometers and according to Uddin (2021), the total population is 6,555,400 [6]. The mean annual temperature is around 26 degrees with average daily range between 21 to 32 degree and receives annual rainfall of 1200 mm [7]. Figure 2 shows the location of the study area.…”
Section: Site Studymentioning
confidence: 99%